Effect of Soft Knee Brace on Shank Movement in Running - Kitagawa, Kodai; Murakami, Tomoya; Wada, Chikamune; Yamamoto, Hiroaki (Poltekkes Kemenkes Jakarta I, 2024)
Background: Soft knee braces are used for the protection and treatment of knee injuries in light-intensity activities of daily life. Soft knee braces have several functions, such as stabilizing and supporting the lower limb posture. However, previous studies did not investigate the effects of a soft knee brace on the lower limbs during vigorous-intensity activities. Aims: The objective of this study was to investigate the effect of a soft knee brace on the physical load and stability of the lower limb during running as a vigorous-intensity activity. Methods: Participants were asked to run with or without a soft knee brace, and lower-limb movements during running were measured using an inertial sensor on the shank. Results: The result showed that soft knee brace significantly reduced the magnitude and mediolateral standard deviation of shank acceleration. Conclusion: The results of this study indicate the possibility that wearing a soft knee brace can improve the physical load and stability of the lower limbs during running.